Gamma-ray attenuation characteristics of polypropylene filled with nano-sized and bulk Bi2O3 and CuO - Gouda Mona M.; Shebly Mona; Habanjar Khulud; Obeid Amro; Awad Ramadan; Badawi Mohamed S. (Nuclear Technology and Radiation Protection)
Polypropylene was produced using compression molding and combined with bulk Bi2O3/CuO, and Bi2O3/CuO nanocomposites at various filler weight fractions (0%, 5%, 10%, 15%, and 20%). Gamma-ray energies from four radioactive sources (241Am, 133Ba, 137Cs, and 60Co), ranging from 59.53 keV to 1332.5 keV, were used to evaluate the radiation attenuation capabilities of the new PP/Bi2O3/CuO polymer composite. Parameters such as the mass attenuation coefficients, total molecular cross-section, effective atomic cross-section, total electronic cross-section, electron density, effective atomic number, half-value layer, tenth value layer, and relaxation length were examined. The results underscored the significant influence of both the size and weight fraction of Bi2O3/CuO fillers on the gamma-ray shielding ability of the polypropylene composite, particularly at lower gamma-ray energy levels. Pure lead, a traditional and widely used shielding material, was used as a reference to assess the effectiveness of the polypropylene composite's half-value layer. Polypropylene composites incorporating nano-sized Bi2O3/CuO exhibited notable improvements in attenuation parameters, highlighting their potential for radiation protection and gamma-ray shielding applications.